2016
DOI: 10.1038/ncomms10743
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of human iPSC-based models for the study and targeting of glioma initiating cells

Abstract: Glioma tumour-initiating cells (GTICs) can originate upon the transformation of neural progenitor cells (NPCs). Studies on GTICs have focused on primary tumours from which GTICs could be isolated and the use of human embryonic material. Recently, the somatic genomic landscape of human gliomas has been reported. RTK (receptor tyrosine kinase) and p53 signalling were found dysregulated in B90% and 86% of all primary tumours analysed, respectively. Here we report on the use of human-induced pluripotent stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 55 publications
0
67
0
2
Order By: Relevance
“…[64] This study and future investigations to identify neural differentiation inducing-factors produced by stromal and stem cells in this co-culture system will enable developing novel protocols to generate neural cells as in this co-culture system but without using feeder cells and eliminate concerns regarding contamination of differentiated cells with stromal cells. Further, stem cell-derived neuronal and glial progenitors can serve as a unique model to study genetic modifications,[65] identify and target specific pathways,[66] and screen compounds for large scale drug discovery. [67]…”
Section: Discussionmentioning
confidence: 99%
“…[64] This study and future investigations to identify neural differentiation inducing-factors produced by stromal and stem cells in this co-culture system will enable developing novel protocols to generate neural cells as in this co-culture system but without using feeder cells and eliminate concerns regarding contamination of differentiated cells with stromal cells. Further, stem cell-derived neuronal and glial progenitors can serve as a unique model to study genetic modifications,[65] identify and target specific pathways,[66] and screen compounds for large scale drug discovery. [67]…”
Section: Discussionmentioning
confidence: 99%
“…There have been no reports of malignant transformation after transplantation in cases of mesenchymal stem cells or other somatic stem cells. In contrast, it has been reported that induced pluripotent stem cells (iPSCs) transformed into tumor stem cells when co-cultured with tumor cells [14]. Consequently, more considerations will be needed for pluripotent stem cell (ESCs/iPSCs)-derived cell products.…”
Section: Translational Medicinementioning
confidence: 89%
“…These cells can be transformed to glioma initiating cells by lentiviral transduction of oncogenes [128]. …”
Section: Preclinical Glioma Modelsmentioning
confidence: 99%